2019
DOI: 10.3390/medicina55120769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2% Chlorhexidine Following Acid Etching on Microtensile Bond Strength of Resin Restorations: A Meta-Analysis

Abstract: Background and Objectives: The aim of this systematic review was to examine the effect of 2% chlorhexidine following acid etching on the microtensile bond strength of resin restorations for different follow-up times. Materials and Methods: A thorough search of PubMed, Scopus, and Embase databases were conducted. In vitro experimental studies or in vivo studies published up to December 2018 with an experimental group treated with a 2% chlorhexidine solution following acid etching and a control group were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…Even though the in vitro studies reported that CHX had the ability to preserve bond‐strength of composite restorations even after 5 years of artificial aging, 23 and to preserve the integrity of the HL after 10 years of aging, 15 all the clinical trials included in this paper clearly demonstrated that CHX did not affect the retention and survival rates of composite restorations placed in NCCL. There are several possible explanations for these observations.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Even though the in vitro studies reported that CHX had the ability to preserve bond‐strength of composite restorations even after 5 years of artificial aging, 23 and to preserve the integrity of the HL after 10 years of aging, 15 all the clinical trials included in this paper clearly demonstrated that CHX did not affect the retention and survival rates of composite restorations placed in NCCL. There are several possible explanations for these observations.…”
Section: Discussionmentioning
confidence: 76%
“…However, the beneficial effect of CHX on resin‐based restorations became evident in the function of time, since significantly higher mean bond‐strength values were observed in groups where CHX was used between phosphoric acid etching step and adhesive application. The reported differences in microtensile bond‐strengths between CHX and control groups were 5.02 MPa, 6.2 MPa and 10.52 MPa for 6, 12 and 24 months, respectively 23 . These values were calculated by the authors of the meta‐analyses, based on the data from the available in vitro studies, and it was speculated that the effect of CHX on bond‐strength is time‐dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marketing authorizations have been granted for treatment of rosacea and periodontal diseases with sub-antimicrobial doses of doxycycline due to MMP inhibition [136][137][138][139][140][141][142]. Interestingly, several disinfectants inhibiting MMPs via cation-chelation are used clinically in dentistry [143][144][145][146][147][148][149][150][151][152]. Aminoglycosides exhibited anti-neoplastic effects as well, which were due to drug-induced increases in readthrough of premature stop codons and not, as expected, inhibition of MMPs due to a lack of chelation with zinc (Table S2).…”
Section: Antibiotics Inhibit Metallo-matrix-proteinasesmentioning
confidence: 99%
“…Dentro del tejido dentinario se ha identificado cuatro tipos de metaloproteinasas (MMP-2 y MMP-9 (gelatinasas), MMP-8 (colagenasa), y MMP-20 (enamelisina)). 6 Las Metaloproteinasas de matriz dentinaria (MMPs), constituyen un factor asociado a la disminución de la longevidad de las restauraciones, ya que son responsables de la degradación del colágeno. 7 Actualmente se han introducido a los protocolos de adhesión de grabado total, la aplicación y frotación de clorhexidina embebida por quince o treinta segundos en el fondo de la cavidad previa a su restauración, este efecto desinfectante elimina potencialmente las bacterias que podrían irritar el tejido pulpar provocando sensibilidad postoperatoria y caries secundaria, además disminuye la degradación de la capa híbrida, inhibiendo la actividad proteolítica de las metaloproteínasas garantizando de manera directa la longevidad de las restauraciones.…”
Section: Introductionunclassified